Bovine recombinant interleukin-2 enhances resistance to bovine herpesvirus-1: Dose response trial - P.G. Reddy; Frank Blecha; J.L. Morrill; H.C. Minocha (Kansas Agricultural Experiment Station Research Reports, 1988)
Twenty-five calves were allotted to five groups: controls that did not receive bovine recombinant interleukin-2 (rIL-2) and four groups that received 5 daily injections of rIL-2 at 11.4, 1.1,0.11, or 0.0 II µg/lb/day. On day 0 of the experiment, all calves received bovine herpesvirus-I (BHV-1) vaccine and the first of the 5 daily injections of bovine rIL-2. All calves were infected with BHV-Ion day 21 of the experiment. Calves treated with 11.4 µg /Ib/day had elevated rectal temperatures and mild diarrhea during administration of rIL2. All other calves were normal. Compared to control calves, those treated with 11.4, 1.1, and 0.11 µg /Ib/day had higher (P<0.05) serum antibody titers to BHV-I and following challenge lower (P<0.05) BRV-1 titers in nasal secretions. Additionally, clinical disease as evidenced by nasal and ocular discharge was less severe. Cytotoxic responses against BHV-I-infected bovine kidney cells were increased (P<0.05) in calves treated with rIL-2 in a dose dependent manner. These data suggest that bovine rIL-2 at doses of 0.11 to 1.1 µg/Ib/day for 5 days may enhance immunity against BHV-I without causing adverse side effects.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Bovine herpesvirus-1; Bovine recombinant interleukin-2; Dose